Analisis Peran Kecerdasan Emosional dan Keterlibatan dalam Pengambilan Keputusan terhadap Komitmen Kerja Guru: Analysis of the Role of Emotional Intelligence and Involvement in Decision-Making on Teachers' Work Commitment - Mohzana Mohzana; Maryanti Maryanti; Desty Endrawati Subroto; Dini Pepilina; Agus Rofi'i; Made Ayu Anggreni (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Several factors influence teachers’ work commitment and students’ academic achievement. These factors include instructors’ emotion regulation skills and their level of involvement in school decision-making. This study aimed to determine how teachers’ emotional intelligence and participation in decision-making influence their dedication to their work. One hundred and fifty educators participated in this quantitative investigation through a survey. Teachers’ emotional intelligence, participation in decision-making, and commitment to their work were assessed using a questionnaire. The impact of these variables was tested through data analysis using regression techniques. Positive and statistically significant effects of emotional intelligence and participation in decision-making on teachers’ dedication to their work were observed. Emotionally intelligent teachers are more dedicated to their jobs because they can better handle stress, form strong relationships with students, and overcome obstacles.Furthermore, being part of the decision-making process fosters a more substantial personal investment in school policies and programs, increasing dedication to the work to improve teachers’ dedication to their work and the quality of education their students receive; this study has significant implications for school administration and professional development programs for educators. This research further examines the real-world consequences for school administrators and policymakers who want to foster an atmosphere encouraging teachers to be emotionally intelligent and have a voice in classroom decisions.